Favourable Lifestyle Protects Cognitive Function in Older Adults With High Genetic Risk of Obesity: A Prospective Cohort Study - Liu, Huamin; Wang, Zhenghe; Zou, Lianwu; Gu, Shanyuan; Zhang, Minyi; Hukportie, Daniel Nyarko; Zheng, Jiazhen; Zhou, Rui; Yuan, Zelin; Wu, Keyi; Huang, Zhiwei; Zhong, Qi; et al. (Frontiers in Molecular Neuroscience, 2022)
The relationship between body mass index (BMI) and cognitive impairment remains controversial, especially in older people. This study aims to confirm the association of phenotypic and genetic obesity with cognitive impairment and the benefits of adhering to a healthy lifestyle. This prospective study included 10,798 participants (age ≥ 50 years) with normal cognitive function from the Health and Retirement Study in the USA. Participants were divided into low (lowest quintile), intermediate (quintiles 2 to 4) and high (highest quintile) groups according to their polygenic risk score (PRS) for BMI. The risk of cognitive impairment was estimated by Cox proportional hazard models. Higher PRS for BMI was associated with increased risk, whereas phenotypic obesity was related to decreased risk of cognitive impairment. Never smoking, moderate drinking and active physical activity were considered favourable, and associated with lower risk of cognitive impairment compared with current smoking, never drinking and inactive, respectively. Favourable lifestyle associated with the low risk of cognitive impairment, even in subjects with low BMI and high PRS for BMI. The present study suggested that regardless of the obesity status, including phenotypic and genetic, adhering to a favourable lifestyle is beneficial to cognitive function.